Use of propranolol for parotid hemangioma. (17th December 2015) - Chang, Lei; Jin, Yunbo; Lv, Dongze; Ying, Hanru; Wang, Tianyou; Qiu, Yajing; Ma, Gang; Chen, Hui; Yu, Wenxin; Yang, Xi; Lin, Xiaoxi
Abstract: Background: Few specific reports have addressed propranolol as a treatment for parotid hemangioma, and its mechanism remains unclear. Methods: Eighty‐seven patients were recruited in this prospective study. Ten patients underwent detailed color Doppler examination. The depths, vessel densities, and resistant indices of 10 lesions were recorded and analyzed before treatment and at 1 and 3 months after treatment. Results: The overall responses were "bad" in 2 cases, "stable" in 4 cases, "good" in 53 cases, and "excellent" in 28 cases. Hemangioma regrowth was observed in 11 cases (12.6%). The parents of 18 patients (20.7%) complained that their children experienced minor discomfort during therapy. The lesion depths, vessel densities, and resistant indices were altered after propranolol treatment. Conclusion: Propranolol can significantly reduce the sizes of parotid hemangiomas with minor side effects. Hemodynamic changes might play an important role in the course of propranolol treatment. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1730–E1736, 2016